A wavelength-tunable and facilely functionable D-A type naphthalene core skeleton: Synthesis, photophysical property, and bio-imaging applications for cells and tissues. (March 2019) - Jung, Yuna; Kim, Youngseo; Kim, Na Hee; Lee, Junho; Kim, Kang-Hoon; Jung, Junyang; Huh, Youngbuhm; Jang, Hyeung-Jin; Joo, Jinmyoung; Park, Sungnam; Kim, Dokyoung
Abstract: A new wavelength-tunable and facilely functionable electron donor (D)-acceptor (A) type fluorescent naphthalene core skeleton and its application for cell membrane imaging are reported. The core skeleton shows bright green fluorescence with aldehyde(CHO) moiety at the electron acceptor site, and its emission wavelength is tuned to blue and red by introducing the moiety of nitrile (CN) and dicyanovinyl (CH(CN)2 ), respectively, at the acceptor site. In addition, the core skeleton can be readily functionable by introducing a targeting moiety at the extra hydroxyl group. For the first demonstration as a fluorescent probe, a long-chain carbon is introduced and evaluated its bio-imaging ability for the cellular membranes on cells and tissues by using confocal laser scanning microscopy (CLSM) and two-photon microscopy (TPM). The synthesis, photophysical property, and quantum chemical calculations are also identified. Graphical abstract: We describe here a fluorescent core skeleton, which is wavelength-tunable, facilely functionable, and one-/two-photon microscopy applicable. Highlights: A wavelength-tunable and facilely functionable D-A type naphthalene core skeleton was developed. The derivative shows bright fluorescence at blue, green, and red region, and its bio-imaging ability was verified in the cells and tissues. The developed core skeleton can be utilized as fluorescent probes with introducing of targeting moieties.